Comparing the mechanical properties of the porcine knee meniscus when hydrated in saline versus synovial fluid. Issue 16 (16th December 2015) - Lakes, Emily H.; Kline, Courtney L.; McFetridge, Peter S.; Allen, Kyle D.
Abstract: As research progresses to find a suitable knee meniscus replacement, accurate in vitro testing becomes critical for feasibility and comparison studies of mechanical integrity. Within the knee, the meniscus is bathed in synovial fluid, yet the most common hydration fluid in laboratory testing is phosphate buffered saline (PBS). PBS is a relatively simple salt solution, while synovial fluid is a complex non-Newtonian fluid with multiple lubricating factors. As such, PBS may interact with meniscal tissue differently than synovial fluid, and thus, the hydration fluid may be an important factor in obtaining accurate results during in vitro testing. To evaluate these effects, medial porcine menisci were used to evaluate tissue mechanics in tension ( n =11) and compression ( n =15). In all tests, two samples from the same meniscus were taken, where one sample was hydrated in PBS and the other was hydrated in synovial fluid. Statistical analysis revealed no significant differences between the mean mechanical properties of samples tested in PBS compared to synovial fluid; however, compressive testing revealed the variability between samples was significantly reduced if samples were tested in synovial fluid. For example, the compressive Young׳s Modulus was 12.69±7.49 MPa in PBS versus 12.34±4.27 MPa in synovial fluid. These results indicate testing meniscal tissue in PBS will largely not affect the mean value of the mechanical properties, but performing compression testing in synovial fluid may provide more consistent results between samples and assist in reducing sample numbers in some experiments.